Foodborne diseases from dairy products in developing countries: Hazards and health implications - Havelaar, A.; Grace, Delia; Wu, F. (University of Florida, 2019)
Dairy products are an important source of high-quality animal proteins in developing countries, and increased consumption of these products by pregnant women and young children is advocated to reduce malnutrition and child stunting. However, the nutritional benefits of dairy products can be compromised by the presence of contaminants causing foodborne disease. These food safety risks are increased by frequent consumption of raw or inadequately heated dairy products. The World Health Organization published estimates of the global burden of foodborne disease in 2015, and attribution of this disease burden to specific food groups in 2017. It is estimated that each year, 600 million people fall ill because of foodborne disease, resulting in 435,000 deaths and a disease burden of 33 million Disability Adjusted Life Years (DALYs; equivalent to one healthy life year lost). Of this burden, 38% is attributed to animal-source foods (ASF), with 12% of the burden of ASF attributed to dairy products. The average global burden of dairy products is 20 DALYs per 100,000 population. The major contaminants in dairy are Mycobacterium bovis (9 DALYs/100,000, highest burden in Africa), Campylobacter spp. (4 DALYs/100,000, highest burden in Eastern Mediterranean), nontyphoidal Salmonella enterica (4 DALYs/100,000, highest burden in Africa) and Brucella spp. (1 DALY/100,000, highest burden in Eastern Mediterranean). The burdens of Cryptosporidium spp., Shiga-toxin producing Escherichia coli and Toxoplasma gondii are low (<1 DALY/100,000). Proper heating of dairy products would be effective in reducing these burdens substantially. The burden of chemical contaminants is less well documented. Adulteration is a potential problem, as illustrated by the melamine contamination incident in Chinese infant formula. Aflatoxin M1 (AFM1) is frequently observed in milk in concentrations higher than maximum tolerable limits in the USA and Europe. AFM1, which cannot be destroyed by heating milk, is a metabolite of aflatoxin B1 (AFB1) - a mycotoxin (fungal toxin) frequently found in corn, nuts, and the feed of dairy animals. However, the carcinogenic potential of AFM1 is significantly lower than that of AFB1, which is a known human liver carcinogen. The risk of liver cancer from current exposure levels to AFM1 is likely to be extremely low. There is limited evidence of an association between AFM1 and stunting, which requires further study. Dioxins cause a high disease burden specifically in Southeast Asia (14 DALYs/100,000); and several metals (lead, arsenic, methylmercury) each cause a global burden of 20-70 DALYs per 100,000. The contribution of dairy products to human exposure to these chemicals is unknown.